NELAYAN VS RENTENIR Studi Ketergantungan Nelayan terhadap Rentenir pada Masyarakat Pesisir - Delmira Syafrini (Jurnal Ilmu Sosial Mamangan, 2014)
The dept and moneylender phenomenon is a problem on fishing communities in Indonesia today. Moneylenders and fishing has become an integral part. Most of fishermen in Indonesia trapped in the vortex of debt to moneylenders as vicious circle that can’t be disconnected. Once they are dealing with a loan shark then lifetime will continue to be pursued and wrapped debt, due to the fact that the interest charged is very high even up to 20-40 percent. So that the nominal amount of debt continues to increase and even not in accordance with the amount of income they get. This paper outlines the fishermen being stuck rentenis and efforts should be made to break the chain of being stuck to the loan shark fishing in accordance with local knowledge